The Evaluation of Drug Related Problems to Patient of Bronchial Asthma Which Has Related With The Duration of Taking Care and Breath Frequency at RSUP Dr M Djamil Padang - Kurniawan, Benny Kurniawan; Khairsyaf, Suhatri S Oea (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: Asthma patients often receive more than one drug and will increase the risk of the occurrence of effect or something unwanted. To deal with Drug-Related Problems (DRPs) in the hospital, the role of pharmacist is needed that is strongly committed and capable of dealing with DRPs is required. This study aims to identify and analyze the DRPs and the relations between DRP and length of stay and also the patient's breathing frequency at RSUP Dr M. Djamil Padang. Data Sources Study Selection: This research is a descriptive research conducted retrospectively. Samples were obtained from patients medical record data during the 2017. Summary of contents of the article: In this study 10 categories of DRPs were analyzed. DRP was occured 19% untreated indications and there was no significant relations between DRP and length of stay and there was no significant relations between DRP and the patient's breathing frequency. Conclusion: The result of statistical test using Spearmen'rho P-value 0.482, there is no significant relation between Drug-Related Problems and length of stay that has the value P>0,05 is the relations between Drug-Related Problems and the breathing of frequency.